Effect of a chelating agent at different pH on the spectroscopic and structural properties of microwave derived hydroxyapatite nanoparticles: A bone mimetic material - Mishra V.K.; Bhattacharjee B.N.; Kumar D.; Rai S.B.; Parkash O. (My University, 2025)
In the present investigation, the effect of a capping agent (EDTA) and pH on the optical and structural characteristics of HAp nanoparticles (NPs) has been studied. Six samples of HAp were synthesized under six different chemical conditions. The HAp specimens were prepared via a microwave irradiation technique (MWIT) in the presence and absence of EDTA at three different pH values 9, 11 and 13. All the samples were calcined at 900 °C. HAp NPs with different sizes and shapes were found to be developed. X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques were employed to determine the crystal structure, crystallite size and bonding parameters of the resulting HAp. The SEM measurements revealed the formation of the different morphologies of the HAp NPs under different physico-chemical conditions. Electron microscopies revealed that the particle size of the samples was in the range of ∼10-200 nm. The TEM results were in good agreement with the SEM results. The study revealed the vital role of the chelating agent (EDTA) in the formation of the pure phase HAp nanostructures. EDTA assisted the formation of needle-like nanorods of HAP and prevented agglomeration. EDTA also prevented carbonate impurities. Carbonate impurities, probably from the atmosphere, were observed in the HAp samples formed without EDTA. Despite the effect of EDTA, the pH of the solution also played a key role in deciding the final morphology of the HAp nanostructures. The samples were also characterized spectroscopically using Fourier transform infrared (FT-IR) spectroscopy and Raman techniques to understand the molecular interactions. The application of laser induced breakdown spectroscopy (LIBS) detected the presence of N and further confirmed the formation of the HAp powders. © 2016 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.